Choreography of early thalamocortical development. - Molnár, Z; Higashi, S; López-Bendito, G (2003)
Thalamic axons, which carry most of the information from the sensory environment, are amongst the first projections to reach the cerebral cortex during embryonic development. It has been proposed that the scaffold of early generated cells in the ventral thalamus, internal capsule and preplate play a pivotal role in their deployment through sharp gene expression boundaries. These ideas were recently evaluated in various strains of mutant mice. In Tbr1, Gbx2, Pax6 KO both thalamic and corticofugal projections fail to traverse the striatocortical junction. In both Emx2 and Pax6 KO brains, the misrouted thalamic afferents are accompanied by displacements of the pioneering projections from the internal capsule. Regardless of their altered route, thalamic afferents in the reeler and L1 KO mice seem to be able to redistribute themselves on the cortical sheet and establish normal periphery-related representation in the somatosensory cortex. Early neural activity delivered through the thalamic projections is thought to be involved in the realignment process of thalamic axons at the time of their accumulation in the subplate layer. However, axonal growth and the early topographic arrangement of thalamocortical fiber pathways appear normal in the Snap25 KO, where action potential mediated synaptic vesicle release is disrupted. We therefore suggest that intercellular communication mediated by constitutive secretion of transmitters or growth factors might play a dominant role during early thalamocortical development.